Fiqh Siyâsah Shar'iyyah Analysis of the Boycott of Pro-Israel Products Based on MUI Fatwa No. 83 of 2023 concerning the Law of Support for the Palestinian Cause - Safdhinar Muhammad An Noor (PT. Banjarese Pacific Indonesia, 2024)
This research article seeks to review and analyze MUI Fatwa No. 83 of 2023 concerning recommendations for calls and calls for boycotts of pro-Israel products based on the views of fiqh siyasah. The aim is to find out how the fiqh siyasah syar'iyyah views the boycott of pro-Israel products as a form of jihad and defense of the Palestinian state after the issuance of the MUI Fatwa ruling. This research uses a type of library research with a descriptive analysis approach. The results of the study found that in the view of fiqh siyasah boycott of pro-Israel affiliated products is mandatory if the boycott is believed to be harmful and difficult to the infidel Zionist Israel, and does not result in mafsadah for Muslims and a larger state than the mafsadah to be minimized. However, if the boycott actually brings violence and adversely affects Muslims, then the law does not become mandatory. Because in the rule that takes precedence is to anticipate the occurrence of mafsadah rather than realizing benefits. This is an effort to weaken the economy so that it can have a significant impact on stopping the military aggression carried out by Israel. That way, it will be very helpful to open a space for conflict peace between the two warring countries. But in various cases, this boycott must also pay attention and consider the negative impacts it causes, so as not to cause violence for Muslims and the country.